2015
DOI: 10.4172/2169-0111.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles of Aralkylamine N-Acetyltransferase, B-cell Translocation Gene-2 and Fatty Acid Synthase in Pasture-based Primiparous Holstein-Friesian Dairy Cows Supplemented with Crude Degummed Canola Oil

Abstract: The effect of oil-rich supplements on the expression of genes involved in lipogenesis and reproduction in pasturebased dairy cows is currently unknown, or at best, scanty and limited to impacts on cow liveweight, body condition score, milk composition, fatty acid and plasma metabolite profiles only. This research investigated the gene expression patterns of Aralkylamine N-acetyltransferase (AANAT), B-cell translocation gene-2 (BTG2) and Fatty Acid Synthase (FASN) genes in response to incremental levels of diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…SCD, FASN, FABP4 and SREBPs are four genes which have become strong candidates for influencing the fat deposition and carcass composition in Eastern Asian cattle breeds and Australian temperate breeds ( Lee & Park, 2016 ; Komatsu et al. 2012 ; Raza et al., 2018 ; Komatsu & Malau-Aduli 2014 ; Malau-Aduli et al. 2015 ).…”
Section: Carcass Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…SCD, FASN, FABP4 and SREBPs are four genes which have become strong candidates for influencing the fat deposition and carcass composition in Eastern Asian cattle breeds and Australian temperate breeds ( Lee & Park, 2016 ; Komatsu et al. 2012 ; Raza et al., 2018 ; Komatsu & Malau-Aduli 2014 ; Malau-Aduli et al. 2015 ).…”
Section: Carcass Qualitymentioning
confidence: 99%
“…Specifically, the effects of FABP4, FASN, SCD and SREBP genes on intramuscular fat and carcass quality ( Takahashi et al. 2016 ; Malau-Aduli et al. 2015 ; Kashani et al.…”
Section: Conclusion: Knowledge Gapsmentioning
confidence: 99%
“…Moderate heritabilities for the whole group of n-3 PUFA were reported by Boichard et al [151] and Maroteau et al [152], and could be explained by major contribution of the shorter chain n-3 PUFA. First identified in the human genome in 2000 [153], fatty acid desaturase 1 and 2 (FADS1 and FADS2) are considered as the major candidate genes that regulate the endogenous synthesis of n-3 LC-PUFA from ALA in mammals including ruminants [154,155,156,157,158]. The first effort to define the association between these two encoding genes and n-3 PUFA in the milk of Holstein cows [159] found that three significant single nucleotide polymorphism (SNP) markers within FADS1 and FADS2 were associated with EPA.…”
Section: Recent Attempts To Increase N-3 Pufa Content In Dairy-dermentioning
confidence: 99%